Higher extracellular fluid volume in women is concealed by scaling to body surface area. (October 2013) - Peters, A. Michael; Seshadri, Nagabhushan; Neilly, Mark D. J.; Perry, Laura; Hooker, Claire A.; Howard, Bethany; Sobnack, Ravin; Irwin, Andrew; Dave, Surendra; Snelling, Hayley; Gruning, Thomas; Patel, Neva H.; et al.
Abstract Objective. The objective was to assess body surface area (BSA) for scaling extracellular fluid volume (ECV) in comparison with estimated lean body mass (LBM) and total body water (TBW) across a range of body mass indices (BMI). Methods. This was a multi-centre study from 15 centres that submitted raw data from routine measurement of GFR in potential kidney transplant donors. There were 819 men and 1059 women in total. ECV was calculated from slope-intercept and slope-only measurements of GFR. ECV was scaled using two methods: Firstly, division of ECV by the scaling variable (ratio method), and secondly the regression method of Turner and Reilly. Subjects were placed into five BMI groups: < 20, 20–24.9, 25–29.9, 30–34.9, and 35 + kg/m2. LBM and TBW were estimated from previously published, gender-specific prediction equations. Results. Ratio and regression scaling gave almost identical results. ECV scaled to BSA by either method was higher in men in all BMI groups but ECV scaled to LBM and TBW was higher in women. There was, however, little difference between men and women in respect to ECV per unit weight in any BMI group, even though women have 10% more adipose tissue. The relations between TBW and BSA and between LBM and BSA, but not between LBM and TBW, were different between men and women. Conclusion. Lean tissue in women contains more extracellular water than in men, a difference that is obscured by scaling to BSA. The likely problem with BSA is its insensitivity to body composition.